Mining the Most Influential k-Location Set from Massive Trajectories - Li, Yuhong; Bao, Jie; Li, Yanhua; Wu, Yingcai; Gong, Zhiguo; Zheng, Yu (Proceedings of the 24th ACM International Conference on Advances in Geographical Information Systems, 2016)
Mining the most influential k-location set finds k locations, traversed by the maximum number of unique trajectories, in a given spatial region. These influential locations are valuable for resource allocation applications, such as selecting charging stations for electric automobiles and suggesting locations for placing billboards. This problem is NP-hard and usually calls for an interactive mining processes, e.g., changing the spatial region and k, or removing some locations (from the results in the previous round) that are not eligible for an application according to the domain knowledge. Thus, efficiency is the major concern in addressing this problem. In this paper, we propose a system by using greedy heuristics to expedite the mining process. The greedy heuristic is efficient with performance guarantee. We evaluate the performance of our proposed system based on a taxi dataset of Tianjin, and provide a case study on selecting the locations for charging stations in Beijing.